Development of a low-Reynolds-number k-ω model for FENE-P fluids - Resende, P. R. [UNESP]; Pinho, F. T.; Younis, B. A.; Kim, K.; Sureshkumar, R. (Springer Nature, 2013)
A low-Reynolds-number k-ω model for Newtonian fluids has been developed to predict drag reduction of viscoelastic fluids described by the FENE-P model. The model is an extension to viscoelastic fluids of the model for Newtonian fluids developed by Bredberg et al. (Int J Heat Fluid Flow 23:731-743, 2002). The performance of the model was assessed using results from direct numerical simulations for fully developed turbulent channel flow of FENE-P fluids. It should only be used for drag reductions of up to 50 % (low and intermediate drag reductions), because of the limiting assumption of turbulence isotropy leading to an under-prediction of k, but compares favourably with results from k-ε models in the literature based on turbulence isotropy. © 2012 Springer Science+Business Media Dordrecht.
Keywords: Drag reduction; FENE-P; k-ω turbulence model; Polymer solutions; FENE-P model; Heat fluid flow; Low Reynolds number; Newtonian fluids; Turbulent channel flows; Visco-elastic fluid; Turbulence models